A catalyst for preparing higher carbon olefins and its preparation method and application
By using SO42-/SiO2/ZrO2/Al2O3 and La2O3/SiO2/TiO2/Al2O3 molecular sieve system catalysts, low-concentration mixed C4 olefins are oligomerized to prepare carbon dodecenes, which solves the problem of low selectivity in the existing technology and achieves high efficiency. , centralized distribution of carbon olefin production.
Patent Information
- Application Number
- CN202310073073.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-01-17
AI Technical Summary
In the prior art, the selectivity of synthesizing carbon dodecanolefins using mixed butene as raw material is low, and it is difficult to effectively utilize low-value mixed butenes after isobutene extraction by refineries.
SO42-/SiO2/ZrO2/Al2O3 and La2O3/SiO2/TiO2/Al2O3 molecular sieve systems are used as catalysts, prepared through hydrothermal reaction and impregnation methods, and used for the oligomerization of low-concentration mixed C4 olefins to prepare carbon dodecenes.
The conversion rate of C4 olefins is 70-83%, the selectivity of C8 olefins is 45-60%, and the selectivity of C12 olefins is 30-42%. The product carbon number distribution is more concentrated, which solves the problem of efficient utilization of low-value mixed butenes.
Smart Images

Figure HDA0004065325670000011 
Figure HDA0004065325670000012 
Figure HDA0004065325670000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic structure catalytic materials, and in particular to a catalyst for preparing higher carbon olefins and a preparation method and application thereof. Background Art
[0002] Olefin polymerization is an important type of chemical reaction that provides an effective way to synthesize liquid fuels, plastics, drugs, dyes, resins, detergents, lubricants and additives. Refineries and petrochemical plants produce a large amount of C4 olefins as by-products, and catalytic polymerization of olefins is an important way to comprehensively utilize C4 olefins. At present, the chemical utilization rate of mixed butenes (including 1-butene, cis-2-butene and trans-2-butene) is very low. Therefore, the chemical utilization of a large amount of excess and low-value butene has become one of the problems that petrochemical companies urgently need to solve. So far, researchers have developed a series of schemes for utilizing butene, such as butene alkylation reaction, butene polymerization reaction, and the production of methyl ethyl ketone, sec-butyl alcohol, sec-butyl acetate and other processes from butene.
[0003] Among the many butene utilization schemes, butene polymerization reaction and its process are receiving more and more attention. At present, the catalysts used for butene polymerization mainly include solid phosphoric acid catalysts, molecular sieve catalysts, nickel catalysts and resin catalysts; and most of the research is carried out around the polymerization of isobutylene, and the product is also a mixed olefin with a wide carbon number distribution. The product is mostly used to produce high-octane gasoline and as a diesel blending component.
[0004] The Chinese patent document with publication number CN 1391542 A discloses a method for preparing C 13 -alcohol mixture method, wherein 60-90% of butene is used as raw material and nickel-containing catalyst is used to synthesize dodecene. However, the selectivity of synthesizing carbon dodecene using mixed butene as raw material needs to be improved. Summary of the invention
[0005] In view of this, the present invention provides a catalyst for preparing high-carbon olefins, and a preparation method and application thereof. By using the catalyst of the present invention, C4 olefins can be mixed at low concentrations to polymerize to prepare polyolefins such as C12 olefins, and the carbon number distribution concentration of the product is higher.
[0006] The present invention provides a catalyst for preparing high carbon olefins, which comprises a main component and an auxiliary component, wherein the main component is SO4 2- / SiO2 / ZrO2 / Al2O3 molecular sieve system, in which SO4 2- The content is 7-10%, the SiO2 content is 50-70%, the ZrO2 content is 9-12%, and the Al2O3 content is 10-30%;
[0007] The auxiliary component is a La2O3 / SiO2 / TiO2 / Al2O3 molecular sieve system, wherein the La2O3 content is 5-10%, the SiO2 content is 75-80%, the TiO2 content is 5-10%, and the Al2O3 content is 1-5%.
[0008] In an embodiment of the present invention, the specific surface area of the main component is 260-290m 2 / g, total pore volume is 0.5-0.7cm 3 / g, and the average pore size is 10-15 nm.
[0009] In the embodiment of the present invention, the specific surface area of the auxiliary component is 280-330 m 2 / g, total pore volume is 0.3-0.5cm 3 / g, and the average pore size is 4-6 nm.
[0010] The present invention provides a method for preparing the catalyst as described above, comprising:
[0011] The pseudo-boehmite is subjected to hydrothermal reaction with silica sol, zirconium sulfate and ammonium sulfate in proportion to obtain the main component;
[0012] The auxiliary component is obtained by hydrothermal synthesis using a certain proportion of γ-Al2O3, lanthanum nitrate, tetraethyl orthosilicate and tetrabutyl titanate as raw materials;
[0013] The main component and the auxiliary component together constitute a catalyst for preparing higher carbon olefins.
[0014] In an embodiment of the present invention, during the preparation of the main component, the pseudo-boehmite is firstly modified by soaking in phosphoric acid, and then immersed in water for hydrothermal reaction.
[0015] In an embodiment of the present invention, during the preparation of the auxiliary component, diquaternary amine is used as a template, and the hydrothermal synthesis includes: crystallization at 140-170° C., filtration and drying, and then calcination at 400-500° C.
[0016] The present invention provides a method for preparing carbon dodecene, comprising:
[0017] A butene mixture is used as a raw material and reacted under the action of the catalyst to obtain carbon dodecene.
[0018] In an embodiment of the present invention, the butene mixture used includes: 1-butene content 11-25%, cis-butene content 10-18%, and trans-butene content 12-27%.
[0019] In an embodiment of the present invention, before the reaction, the catalyst is activated in a nitrogen atmosphere, the allowable pressure range is 0.1-0.3 MPa, the allowable temperature range is 300-500° C., and the activation time is 3-8 h.
[0020] In the embodiment of the present invention, the reaction is carried out in a fixed bed reactor at a temperature of 170-200°C, a pressure of 3-6 MPa, and a volume space velocity of 0.4-0.6 h -1 .
[0021] At present, there are almost no reports on catalysts for synthesizing C12 olefins with high selectivity using low-concentration mixed butene as raw materials. The present invention is based on a full understanding of the above problems and is designed to specifically solve the problem of developing high-value utilization of mixed butene after isobutylene is extracted from refineries, a low-value material.
[0022] The present invention provides a catalyst for preparing high-carbon olefins, and uses the catalyst in a method for preparing polyolefins by oligomerization of low-concentration mixed C4 olefins. In the application method, the oligomerization catalyst is composed of an auxiliary component (auxiliary catalytically active component) and a main component (catalytically active main component), and the main component is a specific SO4 2- / SiO2 / ZrO2 / Al2O3 molecular sieve system, the auxiliary component is La2O3 / SiO2 / TiO2 / Al2O3 molecular sieve system. The catalyst of the present invention is suitable for mixed C4 after isobutylene extraction as raw material, using a fixed bed reactor, and reacting under certain conditions; the experimental results include: C4 olefin conversion rate 70-83%, C8 olefin selectivity 45-60%, C12 olefin selectivity 30-42%, and the remaining components are C16 olefins. The catalyst described in the present invention is mainly to deeply analyze the olefin polymerization reaction mechanism, and to achieve controllable production of olefins with different carbon numbers by innovatively regulating the acid distribution of the catalyst, and the product carbon number distribution concentration is higher (mainly C8 olefins and C12 olefins, and the selectivity of other olefins is less than 5%).
[0023] The embodiment of the present invention adopts an impregnation method and a hydrothermal synthesis method to compound the catalyst. The auxiliary catalytic components and the main catalytic components work synergistically to make the raw material adaptability wider. The yield and distribution of the product and the long-term stability can be guaranteed by adjusting the changes in the catalyst components, thereby achieving a narrow distribution of the carbon number of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The selectivity result of the catalyst application in Example 1;
[0025] Figure 2 The selectivity result of the catalyst application in Example 2;
[0026] Figure 3 The selectivity result of the catalyst used in Example 3;
[0027] Figure 4 The selectivity result of the catalyst application in Example 4;
[0028] Figure 5 The selectivity result of the catalyst application in Example 5;
[0029] Figure 6 This is the selectivity result of the catalyst used in Comparative Example 1. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0031] The present invention provides a catalyst for preparing high carbon olefins, which comprises a main component and an auxiliary component, wherein the main component is SO4 2- / SiO2 / ZrO2 / Al2O3 molecular sieve system, in which SO4 2- The content is 7-10%, the SiO2 content is 50-70%, the ZrO2 content is 9-12%, and the Al2O3 content is 10-30%;
[0032] The auxiliary component is a La2O3 / SiO2 / TiO2 / Al2O3 molecular sieve system, wherein the La2O3 content is 5-10%, the SiO2 content is 75-80%, the TiO2 content is 5-10%, and the Al2O3 content is 1-5%.
[0033] By using the catalyst of the present invention, C4 olefins can be mixed at low concentrations to prepare polyolefins such as C12olefins, and the carbon number distribution of the product is more concentrated.
[0034] The catalyst provided in the embodiment of the present invention is composed of a main catalytic component (or main active component) and an auxiliary catalytic component. The main catalytic component is referred to as the main component and is SO4 2- / SiO2 / ZrO2 / Al2O3 molecular sieve system, its components include silicon dioxide (SiO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), sulfate, specific mass ratio: SO4 2- The content is 7-10%, the SiO2 content is 50-70%, the ZrO2 content is 9-12%, and the Al2O3 content is 10-30%.
[0035] As a preference, the composition ratio of the main catalytic component is: SO42- Content is 9%, SiO2 content is 60%, ZrO2 content is 10%, and Al2O3 content is 20%.
[0036] Furthermore, the main component has a molecular sieve structure, and the BET specific surface area is preferably 260-290 m 2 / g; total pore volume is 0.5-0.7 cm 3 / g, and the average pore size is 10-15 nm. Its optimal structural parameters include: specific surface area of 281m 2 / g, total pore volume 0.55cm 3 / g, average pore size 11.36nm.
[0037] At the same time, the embodiment of the present invention uses auxiliary components to compound the catalyst, and the auxiliary components are a specific La2O3 / SiO2 / TiO2 / Al2O3 molecular sieve system. Its components include lanthanum oxide (La2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), and aluminum oxide (Al2O3). The specific mass ratio is: La2O3 content is 5-10%, SiO2 content is 75-80%, TiO2 content is 5-10%, and Al2O3 content is 1-5%. The modified catalyst developed in the embodiment of the present invention mainly achieves high selectivity distribution of C8 olefins and C12 olefins by regulating the acid distribution of the catalyst.
[0038] In a preferred embodiment of the present invention, the auxiliary component composition ratio is: La2O3 content 10%, SiO2 content 77%, TiO2 content 10%, Al2O3 content 3%; its molecular sieve structure parameters preferably include: specific surface area of 280-330 m 2 / g, with a total pore volume of 0.3-0.5 cm 3 / g, and the average pore size is 4-6 nm. Furthermore, the optimal structure of the auxiliary component is: specific surface area 293 m 2 / g, total pore volume 0.42 cm 3 / g, average pore size 5 nm.
[0039] Preferably, the composite volume ratio of the main catalytic component (referred to as the main agent) and the auxiliary component (auxiliary agent) is 1:0.5-1.5, specifically, the main agent and the auxiliary agent each account for 5 mL.
[0040] Specifically, the present invention provides a method for preparing the catalyst as described above, comprising:
[0041] The pseudo-boehmite is subjected to hydrothermal reaction with silica sol, zirconium sulfate and ammonium sulfate in proportion to obtain the main component;
[0042] The auxiliary component is obtained by hydrothermal synthesis using a certain proportion of γ-Al2O3, lanthanum nitrate, tetraethyl orthosilicate and tetrabutyl titanate as raw materials;
[0043] The main component and the auxiliary component together constitute a catalyst for preparing higher carbon olefins.
[0044] The preparation process of the main catalytic component is as follows: (1) mainly adopting the method of impregnation hydrothermal reaction, preferably pouring silica sol, zirconium sulfate and ammonium sulfate solution into the treated 10-20 mesh modified Al2O3 carrier according to the above proportion, stirring evenly, and then placing it at room temperature for 24 hours, drying at 100-110°C for 3-5 hours, and calcining at 400-500°C for 4-5 hours to obtain the catalytic component; (2) The specific surface area of the obtained main catalytic component is 260-290m 2 / g, total pore volume 0.5-0.7 cm 3 / g, average pore size 10-15nm; (3) The modified Al2O3 can be obtained by soaking commercially available pseudo-boehmite in 2wt% phosphoric acid. In some embodiments, commercially available dry glue (corresponding to pseudo-boehmite) is used as the carrier, and the specific surface area of the unmodified alumina carrier is 336.8m 2 / g, total pore volume 0.67cm 3 / g, average pore size 8 nm; the specific surface area of the alumina carrier after phosphoric acid modification is 345.2 m 2 / g, total pore volume 0.69cm 3 / g, average pore size 7 nm.
[0045] In a preferred embodiment of the present invention, the preparation of the auxiliary catalytic component is as follows:
[0046] The auxiliary catalytic component is prepared by hydrothermal synthesis, preferably using SDA (diquaternary amine) as a template, and the amount can be 0.5% of the SiO2 content. Dissolve SDA in ethanol according to the above ratio and place it in a three-necked flask, and stir it at 40-60°C for 20-60 minutes. Add γ-Al2O3 and lanthanum nitrate solution to the flask and continue stirring. Dissolve tetraethyl orthosilicate and tetrabutyl titanate in ethanol as titrant and start titration. The titration speed is one drop every 3 seconds. After the titration is completed, continue stirring for 1 hour; transfer the synthesized mother liquor to a stainless steel crystallization kettle with a polytetrafluoroethylene lining, preferably crystallize at 140-170°C for at least 24 hours. Filter and dry, and calcine at 400-500°C for 3-5 hours to obtain the auxiliary catalytic component; (2) The specific surface area of the prepared auxiliary catalytic component is 288-327 m 2 / g, total pore volume 0.37-0.46 cm 3 / g, average pore size 4-6 nm; its optimal structure is: specific surface area 293 m 2 / g, total pore volume 0.42 cm 3 / g, average pore size 5 nm.
[0047] Specifically, according to the principle agent and the auxiliary agent each accounting for 5 mL, the above-prepared catalytic components are compounded in the embodiment of the present invention to obtain the catalyst.
[0048] The embodiment of the present invention provides a method for preparing carbon dodecene, comprising:
[0049] A butene mixture is used as a raw material and reacted under the action of the catalyst as described above to obtain carbon dodecene.
[0050] The method for preparing carbon dodecene using the above catalyst of the present invention can also be a method for evaluating high carbon olefin catalysts. In an embodiment of the present invention, the evaluation process uses a butene mixture as a raw material and uses a fixed bed reactor for catalytic reaction. The fixed bed reactor is a reactor in which a granular solid catalyst is loaded to form a stacked bed layer of a certain height, and the gas material flows through the static fixed bed layer through the gaps between the particles to realize a heterogeneous reaction process.
[0051] The butene mixture used in the embodiment of the present invention contains four isomers of butene, specifically including: 1-butene content 11-25%, cis-butene content 10-18%, trans-butene content 12-27%, and isobutylene content less than 1%. For example, the raw materials of this application are mainly composed of 1-butene content 12%, cis-butene content 10%, and trans-butene content 13%. In addition, the experimental raw materials require an isobutylene content of less than 1.0%, an alkane content of 54-60%, a 1,3-butadiene content of less than 0.3%, a sulfur content of less than 0.5 mg / kg, and a trace water content of less than 20 mg / kg.
[0052] Before the reaction, the catalyst is preferably activated in a nitrogen atmosphere in the embodiment of the present invention; during activation, the pressure allowable range is 0.1-0.3MPa, the temperature allowable range is 300-500°C, the activation time is 3-8h, and the nitrogen flow rate is adjusted according to the catalyst loading amount. In some experiments, the present invention is specifically carried out on a 10ml fixed bed, the main agent and the auxiliary agent each account for 5mL, and the nitrogen flow rate can be set to 100ml / min.
[0053] The fixed bed reactor used in the embodiment of the present invention preferably has an operating temperature of 170-200°C, an operating pressure of 3-6 MPa, and a volume space velocity of 0.4-0.6 h -1 .
[0054] The optimal solution determined by experimental screening is as follows: the activation conditions are: under a slight positive pressure of 0.1 MPa, a gas-solid volume ratio of 10:1, and activation at 500°C for 6 hours; the evaluation conditions are: at a reaction temperature of 180°C, a system pressure of 6 MPa, and a volume space velocity of 0.6 h -1 Under the condition of liquid-solid phase reaction.
[0055] The catalyst prepared in the embodiment of the present invention is suitable for using mixed C4 after isobutylene extraction as raw material, and adopts a fixed bed reactor to catalyze olefin polymerization, which can achieve high selectivity distribution of C8 olefins and C12 olefins. Experiments show that the conversion rate of C4 olefins can reach 70-83%; the selectivity of C8 olefins is 45-60%, the selectivity of C12 olefins is 30-42%, and the selectivity of C16 olefins is 1-2%, and the carbon number distribution concentration of the products is higher.
[0056] In order to better understand the technical content of the present invention, specific examples are provided below to further illustrate the present invention. In the following examples, raw materials such as alumina are commercially available. The mixed C4 raw material is mainly composed of 1-butene content of 12%, cis-butene content of 10%, and trans-butene content of 13%; the isobutylene content is less than 1.0%, the alkane content is 54-60%, the 1,3-butadiene content is less than 0.3%, the sulfur content is less than 0.5 mg / kg, and the trace water content is less than 20 mg / kg. Example 1
[0057] Catalyst preparation:
[0058] Lanthanum nitrate, tetraethyl orthosilicate, tetrabutyl titanate, and γ-Al2O3 are used as raw materials, and SDA is used as a template agent in an amount of 0.5% of the SiO2 content. According to the ratio of La2O3 10%, SiO2 77%, TiO2 10%, and Al2O3 3%, the auxiliary catalytic component is synthesized by hydrothermal method; SDA is dissolved in ethanol according to the above ratio and placed in a three-necked flask, stirred at 50°C for 30 minutes, γ-Al2O3 and lanthanum nitrate solution are added to the flask and continued to stir, tetraethyl orthosilicate and tetrabutyl titanate are dissolved in ethanol, and titration is started. The titration speed is one drop every 3 seconds, and stirring is continued for 1 hour after the titration is completed. The synthesized mother liquor is transferred to a stainless steel crystallization kettle with a polytetrafluoroethylene lining, crystallized at 170°C for 24 hours, filtered and dried, and calcined at 500°C for 4 hours to obtain (the preparation conditions of the following examples are basically the same).
[0059] Zirconium sulfate, silica sol, and pseudo-boehmite are used as raw materials (extruded and modified by immersion in 2% phosphoric acid. The specific surface area of the modified carrier is 345.2 m 2 / g, total pore volume 0.69 cm 3 / g, average pore size 7 nm), according to SO4 2-9%, SiO2 60%, ZrO2 10%, Al2O3 20%, the main catalytic component is prepared by impregnation and hydrothermal reaction; according to the above proportions, silica sol, zirconium sulfate and ammonium sulfate solution are poured into the modified Al2O3 carrier (10-20 mesh), stirred evenly and placed at room temperature for 24 hours, dried at 110°C for 3 hours, and calcined at 500°C for 4 hours to obtain (the preparation conditions of the following examples are basically the same).
[0060] According to the BET test, the specific surface area of the prepared auxiliary catalytic component is 293m 2 / g, total pore volume 0.42cm 3 / g, average pore size 5nm; specific surface area of main catalytic component 281m 2 / g, total pore volume 0.55cm 3 / g, average pore size 11.36nm.
[0061] Activation stage:
[0062] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.1 MPa for 6 h.
[0063] Evaluation stage:
[0064] Using a fixed bed reactor, the bed layer is 10 ml, the reaction temperature is 180 ° C, the system pressure is 6 MPa, and the volumetric space velocity is 0.6 h -1 , run for 200h. C4 conversion rate 78-83%, C8 selectivity 53-56%, C12 selectivity 38-42%; the results are as follows Figure 1 shown.
[0065] The fixed bed is a conventional device, the reactor has a height-to-diameter ratio of 10, the catalyst volume is 10 ml, and the auxiliary agent and main agent are 5 ml each.
[0066] The product selectivity was tested by gas chromatography; analytical instrument model: Agilent 7890B gas chromatograph.
[0067] Analytical method (C4C9 alcohol method): Inlet temperature: 250℃, detector temperature: 290℃, programmed temperature rise steps: 50℃ for 2min, the first stage is heated to 100℃ at a rate of 10℃ / min and retained for 5min; the second stage is heated to 150℃ at a rate of 5℃ / min; the third stage is heated to 280℃ at 25℃ / min and retained for 5min.
[0068] Result processing: Cyclopentane in the mixed C4 raw material was used as the internal standard to determine its composition. The data processing adopted the peak area normalization method, retaining the C4 component peak, C8 component peak, C12 component peak, and C16 component peak. Accordingly, the C4 conversion rate, C8 selectivity, C12 selectivity, and C16 selectivity can be roughly calculated by formulas (1)-(4):
[0069] .
[0070] Where S C4 is the peak area of the C4 component peak in the chromatographic results, S C8 is the peak area of the C8 component peak in the chromatographic results, S C12 is the peak area of the C12 component peak in the chromatographic results, S C16 It is the peak area of the C16 component peak in the chromatographic results.
[0071] Example 2
[0072] Catalyst preparation:
[0073] Lanthanum nitrate, tetraethyl orthosilicate, tetrabutyl titanate, SDA, and γ-Al2O3 were used as materials, and the auxiliary catalytic component was synthesized by hydrothermal method in the proportion of La2O3 10%, SiO2 77%, TiO2 10%, and Al2O3 3%. Zirconium sulfate, silica sol, and pseudo-boehmite were used as raw materials (extruded strips were required, phosphoric acid modification was not used, and the specific surface area was 336.8m 2 / g, total pore volume 0.67cm 3 / g, average pore size 8nm), according to SO4 2- The main catalytic component is prepared by impregnation and hydrothermal reaction in a ratio of 9%, SiO260%, ZrO210%, and Al2O320%.
[0074] Among them, the auxiliary agent structure remains unchanged. No phosphoric acid-modified main agent is used, with a specific surface area of 287m 2 / g, pore volume 0.52cm 3 / g, average pore size 11.03nm.
[0075] 5 ml of auxiliary agent and main agent respectively, the preparation parameters are the same as those in Example 1. Activation stage:
[0076] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.1 MPa for 6 h.
[0077] Evaluation stage:
[0078] Reaction temperature 180℃, system pressure 6Mpa, volumetric space velocity 0.6h -1, run for 200h. C4 conversion rate 58-72%, C8 selectivity 53-56%, C12 selectivity 21-38%; the results are as follows Figure 2 shown.
[0079] Example 3
[0080] Catalyst preparation:
[0081] Lanthanum nitrate, tetraethyl orthosilicate, tetrabutyl titanate, SDA, and γ-Al2O3 were used as raw materials, and the auxiliary catalytic component was synthesized by hydrothermal method in the ratio of La2O3 10%, SiO2 77%, TiO2 10%, and Al2O3 3%. Zirconium sulfate, silica sol, and pseudo-boehmite were used as raw materials (extruded strips and modified with phosphoric acid were required), and SO4 2- The main catalytic component is prepared by impregnation and hydrothermal reaction in a ratio of 11% (1% ammonium sulfate is added), SiO257%, ZrO210%, and Al2O320%.
[0082] The auxiliary agent structure remains unchanged; the main agent structure has a specific surface area of 332m 2 / g, pore volume 0.51cm 3 / g, pore size 10.86nm. Activation stage:
[0083] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.2 MPa for 6 h.
[0084] Evaluation stage:
[0085] Reaction temperature 180℃, reaction pressure 6Mpa, volumetric space velocity 0.6h -1 , C4 conversion rate 75-78%, C8 selectivity 52-56%, C12 selectivity 32-36%. After 220h of operation, C4 conversion rate dropped to 60%; the results are as follows Figure 3 shown.
[0086] Example 4
[0087] Catalyst preparation:
[0088] Lanthanum nitrate, tetraethyl orthosilicate, tetrabutyl titanate, SDA, and γ-Al2O3 were used as raw materials, and the auxiliary catalytic component was synthesized by hydrothermal method in the ratio of La2O3 10%, SiO2 77%, TiO2 10%, and Al2O3 3%. Zirconium sulfate, silica sol, and pseudo-boehmite were used as raw materials (extruded strips and modified with phosphoric acid were required), and SO4 2- The main catalytic component is prepared by impregnation in the ratio of 9%, SiO2 57%, ZrO2 13%, and Al2O3 20%.
[0089] The auxiliary agent structure has not changed, and the main agent has a specific surface area of 281m2 / g, pore volume 0.52cm 3 / g, pore size 11.20nm. Activation stage:
[0090] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.1 MPa for 6 h.
[0091] Evaluation stage:
[0092] Reaction temperature 180℃, system pressure 6Mpa, volumetric space velocity 0.6h -1 After 200 hours of operation, the C4 conversion rate was 68-72%, the C8 selectivity was 53-55%, and the C12 selectivity was 37-42%. Figure 4 shown.
[0093] Example 5
[0094] Catalyst preparation:
[0095] Lanthanum nitrate, tetraethyl orthosilicate, tetrabutyl titanate, SDA, and γ-Al2O3 were used as raw materials, and the auxiliary catalytic component was synthesized by hydrothermal method in the ratio of La2O3 10%, SiO2 77%, TiO2 10%, and Al2O3 3%. Zirconium sulfate, silica sol, and pseudo-boehmite were used as raw materials (extruded strips and modified with phosphoric acid were required), and SO4 2- The main catalytic component is prepared by impregnation in a ratio of 9%, SiO260%, ZrO210%, and Al2O320%.
[0096] The specific surface area of the prepared auxiliary catalytic component is 293m 2 / g, total pore volume 0.42 cm 3 / g, average pore size 5nm; specific surface area of main catalytic component 231m 2 / g, total pore volume 0.37cm 3 / g, average pore size 8nm.
[0097] Activation stage:
[0098] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.1 MPa for 6 h.
[0099] Evaluation stage:
[0100] The reaction temperature was 180°C, the system pressure was 6 MPa, the volumetric space velocity was 0.6 h-1, and the operation time was 200 h. The C4 conversion rate was 35-46%, the C8 selectivity was 45-51%, and the C12 selectivity was 15-23%. The results are as follows Figure 5 shown.
[0101] Comparative Example 1
[0102] Catalyst preparation:
[0103] Zirconium sulfate, silica sol, pseudo-boehmite as raw materials (need to be extruded and phosphoric acid modified), according to SO4 2- 9%, SiO260%, ZrO210%, Al2O320% in the ratio, and it is prepared by impregnation and hydrothermal reaction.
[0104] Activation stage:
[0105] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.1 MPa for 6 h.
[0106] Evaluation stage:
[0107] The reaction temperature was 180°C, the reaction pressure was 6 MPa, and the feed was started. The volumetric space velocity was 0.6 h -1 , C4 conversion rate 69-75%, C8 selectivity 52-55%, C12 selectivity 30-35%. After 70h of operation, the conversion rate dropped to 60%; the results are as follows Figure 6 shown.
[0108] Comparative Example 2
[0109] Catalyst preparation:
[0110] Lanthanum nitrate, tetraethyl orthosilicate, tetrabutyl titanate, SDA and γ-Al2O3 were used as raw materials, and the catalyst was synthesized by hydrothermal method in the ratio of La2O3 10%, SiO2 77%, TiO2 10% and Al2O3 3%.
[0111] Activation stage:
[0112] The nitrogen flow rate was 100 ml / min, the temperature was raised to 500°C at a heating rate of 3°C / min, and activated at 0.1 MPa for 6 h.
[0113] Evaluation stage:
[0114] The reaction temperature was 180°C, the reaction pressure was 6 MPa, and the feed was started. The volumetric space velocity was 0.6 h -1 , no product is generated.
[0115] From the above examples, it can be seen that in the catalyst compound of the present invention, the main component is a specific SO4 2- / SiO2 / ZrO2 / Al2O3 molecular sieve system, and the auxiliary component is La2O3 / SiO2 / TiO2 / Al2O3 molecular sieve system. The catalyst of the present invention is suitable for mixed C4 after isobutylene extraction as raw material, using a fixed bed reactor, and reacting under certain conditions; the experimental results include: C4 olefin conversion rate 70-83%, C8 olefin selectivity 45-60%, C12 olefin selectivity 30-42%, and the remaining components are C16 olefins. The catalyst of the present invention is mainly based on an in-depth analysis of the olefin polymerization reaction mechanism, and realizes the controllable production of olefins with different carbon numbers by innovating the acid distribution of the catalyst, and the product carbon number distribution concentration is higher.
[0116] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the inventive concept and technical solution to other occasions without improvement, should be regarded as the protection scope of the present invention.
Claims
1. A catalyst for preparing higher olefins, characterized in that: It includes a main component and an auxiliary component, wherein the main component is SO4 2- / SiO2 / ZrO2 / Al2O3 molecular sieve system, in which SO4 2- The content is 7-10%, the SiO2 content is 50-70%, the ZrO2 content is 9-12%, and the Al2O3 content is 10-30%; The auxiliary component is a La2O3 / SiO2 / TiO2 / Al2O3 molecular sieve system, wherein the La2O3 content is 5-10%, the SiO2 content is 75-80%, the TiO2 content is 5-10%, and the Al2O3 content is 1-5%.
2. The catalyst according to claim 1, characterized in that The specific surface area of the main component is 260-290m 2 / g, with a total pore volume of 0.5-0.7 cm 3 / g, and the average pore size is 10-15 nm.
3. The catalyst according to claim 2, characterized in that The specific surface area of the auxiliary component is 280-330 m 2 / g, with a total pore volume of 0.3-0.5 cm 3 / g, and the average pore size is 4-6 nm.
4. The method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: include: The pseudo-boehmite is subjected to hydrothermal reaction with silica sol, zirconium sulfate and ammonium sulfate in proportion to obtain the main component; The auxiliary component is obtained by hydrothermal synthesis using a certain proportion of γ-Al2O3, lanthanum nitrate, tetraethyl orthosilicate and tetrabutyl titanate as raw materials; The main component and the auxiliary component together constitute a catalyst for preparing higher carbon olefins.
5. The preparation method according to claim 4, characterized in that: During the preparation of the main component, the pseudo-boehmite is firstly modified by soaking in phosphoric acid.
6. The preparation method according to claim 4, characterized in that: In the preparation process of the auxiliary component, diquaternary amine is used as a template, and the hydrothermal synthesis includes: crystallization at 140-170° C., filtration and drying, and then calcination at 400-500° C.
7. A method for preparing carbon dodecene, characterized in that: include: A butene mixture is used as a raw material, and a reaction is carried out under the action of the catalyst described in any one of claims 1 to 3 to obtain carbon dodecene.
8. The method for preparing carbon dodecene according to claim 7, characterized in that: The butene mixture used includes: 1-butene content 11-25%, cis-butene content 10-18%, and trans-butene content 12-27%.
9. The method for preparing carbon dodecene according to claim 7, characterized in that: Before the reaction, the catalyst is activated in a nitrogen atmosphere, the allowable pressure range is 0.1-0.3 MPa, the allowable temperature range is 300-500° C., and the activation time is 3-8 hours.
10. The method for preparing carbon dodecene according to claim 7, characterized in that: The reaction is carried out in a fixed bed reactor at a temperature of 170-200°C, a pressure of 3-6 MPa, and a volume space velocity of 0.4-0.6 h -1 .
Citation Information
Patent Citations
C13 alcohol mixture and functionalized C13 alcohol mixture
CN1391542A
Catalyst of preparing C8 and C12 olefin by using butene oligopoly merization and its process
CN1137420A